Fostering empowerment and building capacities of rural women through community-based agroindustry: A case study in Donowarih Village, Indonesia - Suhartini, Sri; Wijana, Susinggih; Putri, Widya Dwi Rukmi; Deoranto, Panji; Rohma, Rohma; Rahma, Novita Ainur; Effendi, Masud (Journal of Innovation and Applied Technology, 2023)
Donowarih village, located in Malang Regency, East Java, Indonesia, is closed to the Universitas Brawijaya’s Educational Forest (known as UB Forest). The village has various potential local commodities such as orange fruits and batik. During harvesting season, the price of orange fruits declined, and inadequate storage system has led to a rapid deterioration of orange fruits. Furthermore, various problems faced by the community, such as poverty and lack of knowledge/skills, are becoming the major challenges to be tackled. On the other hand, orange fruits and batik are potential to be diversified into high value-added products, which can be done through the introduction of post-harvesting technology and trainings for skills improvement. Furthermore, the Indonesian Government program of one village one product (OVOP) is becoming key drivers to any community engagement program in Indonesia.